2018
DOI: 10.1177/2051415818786667
|View full text |Cite
|
Sign up to set email alerts
|

Day-case surgery is possible in the majority of men undergoing transurethral resection of the prostate – a report on over 1000 cases

Abstract: Objective: We describe our experience of performing bipolar transurethral resection in saline (Olympus Medical) as a day-case procedure over an initial five-year period. Patients and methods: All procedures coded as transurethral resection of the prostate over a 60-month period were analysed to determine whether the procedure was planned as a day-case or as an inpatient admission, and whether postoperative discharge proceeded as intended. Re-admission rates, reasons for re-admission and transfusion rates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…9 These pressures are compounded by problems with the availability of inpatient beds which has resulted in planned surgical cases being cancelled on the day of surgery, especially if the indication for the surgical procedure is a benign disease. Partly in response to these pressures more than 90% of our ureteroscopic surgery, 75.2% of our bladder outflow obstruction surgery 17 and 80.1% of our bladder tumour resections are already performed on a day case basis 18 . As a consequence, all facets of our day case pathway, including our waiting list team, preoperative assessment service, and a dedicated urology rapid access clinic staffed by skilled urology nurse practitioners, function in an integrated way and are highly experienced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 These pressures are compounded by problems with the availability of inpatient beds which has resulted in planned surgical cases being cancelled on the day of surgery, especially if the indication for the surgical procedure is a benign disease. Partly in response to these pressures more than 90% of our ureteroscopic surgery, 75.2% of our bladder outflow obstruction surgery 17 and 80.1% of our bladder tumour resections are already performed on a day case basis 18 . As a consequence, all facets of our day case pathway, including our waiting list team, preoperative assessment service, and a dedicated urology rapid access clinic staffed by skilled urology nurse practitioners, function in an integrated way and are highly experienced.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of this should not be underestimated in achieving successful day case surgery ( and may affect other units ability to replicate our experience. 17,18 The recently published review of the MIP system by NICE has shown a cost-benefit of £800.00 when performed as an inpatient procedure compared to standard PCNL. Our cost analysis has shown a broadly similar cost-benefit when comparing both modalities.…”
Section: Discussionmentioning
confidence: 99%
“…The EAC explored the effect of applying to bTURP a reduced length of hospital stay of 0.5 days, reflecting day-case surgery, based on published evidence [ 27 ]. The effect was minimal, with UroLift remaining cost saving relative to all comparators.…”
Section: Cedar’s Review Of the Evidencementioning
confidence: 99%
“…A variety of options now exist to treat benign prostatic enlargement, each with slightly different anticipated long-term efficacy, and sideeffect and risk profiles [5]. There is increasing recognition that TURP and laser enucleation of the prostate can be delivered as day-case procedures within well designed pathways [6,7]. Local anaesthetic treatment options exist and many treatments have been shown to be amenable to being performed as day-case operations [8,9].…”
Section: Introductionmentioning
confidence: 99%